Refuerzo pedagógico y su incidencia en el proceso de lectoescritura en estudiantes de 4to. año EGB de la Unidad Educativa Juan E. Verdesoto de la ciudad de Babahoyo - 2023 - Zambrano Herrera, Mariana Mallerly (2023)
The main objective of the current study was to determine the incidence of pedagogical reinforcement in the literacy process in 4th year EGB students of the Juan E. Verdesoto Educational Unit. The study was carried out using as a sample 10 students from the 4th year of EGB of the Juan E. Verdesoto Educational Unit who had evidenced problems in the assimilation of knowledge and development for which direct observation was used after having been helped by reinforcement. pedagogical and at the same time a documentary review form was also applied to the grade records of said students seeking to find final supporting evidence based on the scores obtained. These results helped to identify that the teacher's intervention when carrying out pedagogical reinforcement based on appropriate strategies and tactics is well received by the student, directly influencing the improvement of their grades, so the reinforcement affects the student's reading and writing process and your personal growth. This study serves as a great contribution in giving value to the pedagogical reinforcement and efforts of EGB teachers who always have to be dedicated to new strategies and techniques to best address the problems that arise in the development of the career, seeking the intellectual, personal and emotional development of the student in their care.